Bilateral estimates for the support of a solution of the Cauchy problem for an anisotropic quasilinear degenerate equation - Degtyarev, S. P.; Tedeev, A. F. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We establish exact-order bilateral estimates for the size of the support of a solution of the Cauchy problem for a doubly nonlinear parabolic equation with anisotropic degeneration in the case where the initial data are finite and have finite mass.